Investigation of cognitive wireless and power line network using internet of things - Roy, Onimesh; Shahriar, Md Atique; Mahmud, Shakib; Komol, Tanjim Ahmed (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.